Pendidikan Islam Dalam Aqiqah: Parenting Anak Usia 10-12 Tahun - Ramadhan Lubis; Tengku Muhammad Alfi Syahrin; Nur Hasanah; Faiz Maulana (Universitas 45 Surabaya, 2023)
Parents as the first educators in the main fund in the family must find information and knowledge on their own about how to grow and support their children's education in positive conditions. The purpose of this study is to find out how to raise children in Islam for children aged 10-12 years. The method used is to use a qualitative descriptive research method with reference sources derived from field observations and using references from the web such as Google Scholar and also other sources from the internet. The results of this study are that the responsibility of parents to care for children does not only apply at the age of 0-3 years, but also until he is an adult, where he still needs support for his education and so on. It is also important for every family to carry out religious practices in accordance with their beliefs and culture, while taking into account the underlying religious values and teaching.